Habakkuk and the problem of suffering: theodicy deferred - Whitehead, Philip (Eisenbrauns, 2016)
A theological reading of the book of Habakkuk offers insight into the problem of suffering. Approaching the text canonically, this study aims to explore Habakkuk’s theological response to suffering, and the potential to relate this to Christian and classically theistic attempts to articulate a theodicy. Although Habakkuk puts forward no theological objection to the idea that the suffering experienced by God’s people is, in some sense, deserved, he nonetheless questions the extent of the suffering and the justice of the God who permits it from a perspective of faith and eschatological hope. The answers to the questions posed by evil and suffering are apparently deferred by Habakkuk, who persists in faith despite the present lack of resolution to these questions. Such a reading lends support to models of theodicy that prioritize the practical dimensions of suffering, and challenges accounts that would insist on satisfactory explanations for suffering as a condition for faith.